PERCENTUAL DE ÓLEO EM CANOLA CULTIVADA SOB DIFERENTES ARRANJOS DE PLANTAS - Kruger, Cleusa A. M. B.; Silva, Adair J. d.; Bach, Sandro; Dambrós, Diego; Santos, Cleverson D. d.; Bandeira, Taiane P.; Batistti, Gabriel C.; Wentz, Renan; Medeiros, Sandro L. P.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo